Operational performance of an STD control programme in Mwanza Region, Tanzania. Issue 6 (1st December 2000) - Grosskurth, Heiner; Mwijarubi, Ezra; Todd, James; Rwakatare, Medard; Orroth, Kate; Mayaud, Philippe; Cleophas, Bernadette; Buvé, Anne; Mkanje, Rashid; Ndeki, Leonard; Gavyole, Awene; Hayes, Richard; et al.
Abstract : Objectives: To describe important details of the design and operational features of the Mwanza sexually transmitted diseases (STD) control programme. To assess the feasibility of the intervention, the distribution of STD syndromes observed, the clinical effectiveness of syndromic STD case management, the utilisation of STD services by the population, and the quality of syndromic STD services delivered at rural health units. Methods: The intervention was integrated into rural primary healthcare (PHC) units. It comprised improved STD case management using the syndromic approach, facilitated by a regional programme office which ensured the training of health workers, a reliable supply of effective drugs, and regular support supervision. Five studies were performed to evaluate operational performance: (i) a survey of register books to collect data on patients presenting with STDs and reproductive tract infections (RTIs) to rural health units with improved STD services, (ii) a survey of register books from health units in communities without improved services, (iii) a survey of register books from referral clinics, (iv) a home based cross sectional study of STD patients who did not return to the intervention health units for follow up, (v) a cross sectional survey of reported STD treatment seeking behaviour in a random cohort of 8845 adults served by rural health units. Results: During the 2 years of the Mwanza trial, 12 895 STD syndromes were treated at the 25 intervention health units. The most common syndromes were urethral discharge (67%) and genital ulcers (26%) in men and vaginal discharge (50%), lower abdominal tenderness (33%), and genital ulcers (13%) in women. Clinical treatment effectiveness was high in patients from whom complete follow up data were available, reaching between 81% and 98% after first line treatment and 97%–99% after first, second, and third line treatment. Only 26% of patients referred to higher levels of health care had presented to their referral institutions. During the trial period, data from the cohort showed that 12.8% of men and 8.6% of women in the intervention communities experienced at least one STD syndrome. Based on various approaches, utilisation of the improved health units by symptomatic STD patients in these communities was estimated at between 50% and 75%. During the first 6 months of intervention attendance at intervention units increased by 53%. Thereafter, the average attendance rate was about 25% higher than in comparison communities. Home visits to 367 non-returners revealed that 89% had been free of symptoms after treatment, but 28% became symptomatic again within 3 months of treatment. 100% of these patients reported that they had received treatment, but only 74% had been examined, only 57% had been given health education, and only 30% were offered condoms. Patients did not fully recall which treatment they had been given, but possibly only 63% had been treated exactly according to guidelines. Conclusions: This study demonstrated that it is feasible to integrate effective STD services into the existing PHC structure of a developing country. Improved services attract more patients, but additional educational efforts are needed to further improve treatment seeking behaviour. Furthermore, clear treatment guidelines, a reliable drug supply system, and regular supervision are critical. All efforts should be made to treat patients on the spot, without delay, as referral to higher levels of care led to a high number of dropouts. The syndromic approach to STD control should be supported by at least one reference clinic and laboratory per country to ensure monitoring of prevalent aetiologies, of the development of bacterial resistance, and of the effectiveness of the syndromic algorithms in use.